'Should have gone to …': bilateral papilloedema with normal CSF pressure due to vestibular schwannoma. Issue 12 (12th December 2020) - Ronan, Geoffrey Peter; Gailani, Gaafar; Costello, Ciara; Sweeney, Brian
Abstract : A 24-year-old woman presented with bilateral blurring of her distance vision and 'dizzy spells'. She had no other neurological symptoms or medical history. She consulted an optometrist, and optical coherence tomography (OCT) was performed, which demonstrated papilloedema. She was referred to the local eye clinic for assessment and from there was referred for neurological assessment. Her initial investigations revealed no abnormalities, and brain imaging was reported to be normal. In the absence of an alternative diagnosis, idiopathic intracranial hypertension (IIH) was considered and a lumbar puncture was performed. This showed elevated protein but normal cerebrospinal fluid (CSF) pressure. MRI of the brain the next day revealed a large cerebellopontine lesion in keeping with vestibular schwannoma. She was referred to neurosurgery for operative management. This case highlights three interesting points: the aetiology of her papilloedema without raised intracranial pressure, the decision to perform a lumbar puncture in suspected IIH and community OCT as a clinical adjunct.